Effect of the Variation of Fiber Percentage in the Gradients of Composite Materials on the Breaking Strength of Concrete Beams - Ahmed Babiker, Mohammed Babiker; Elarabi, Salaheldin M. (Gezira Journal of Engineering and Applied Sciences; Vol 17 No 1 (2022), 2026)
The use of bio-composites to reinforce concrete beams and improve their properties of bearing strength and strain reduces errors of buildings. The aim of this study was to avoid buildings` errors that result from using traditional building materials. Wood, as a building material suffers from strength shortage and fungi attack, whereas steel suffers from corrosion. Composite materials were used to reinforce concrete beams. Three different samples were made by reinforcing epoxy with kenaf and steel fibres. Samples (A, B, and C) were composed of 70%:30%, 50%:50%, and 30%:70% of kenaf to steel respectively. Each sample replaced the cement ingredient in the concrete mixture by 20% weight. The samples were thus: a standard sample which was composed of cement, sand, and concrete together with the other three samples. The procedure of making the concrete beams was implemented by well mixing the components, putting the mixture in the mold for 24 hours, and immersing it in water for 7 and 28 days. The bearing strength test was carried according to the ASTM E4 OR ISO 7500-1. The results taken in the 7 days’ period have shown an average of 12.68 KN, 10.79 KN, and 9.73 KN for samples A, B, and C respectively compared to 15.32 KN for the standard sample. However, the results for the 28 days for the samples A, B, and C were 17.86 KN, 15.41 KN, 14.1 KN respectively, compared to 21.38 KN for the standard sample. Thus, sample A (kenaf to steel ratio of 70%: 30%) has had the best breaking strength compared to the other two samples taking the standard sample as the reference sample.